THE EFFECTIVENESS OF STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) AND TEAMS GAMES TOURNAMENTS (TGT) TECHNIQUE TOWARD STUDENTS’ SPEAKING ABILITY AT TENTH GRADE OF SMA NEGERI 1 PAGAR DEWA ACADEMIC YEAR 2014/2015 - Andri Yono (Jurnal Pedagogy, 2015)
The researchers offer some techniques to be applied in speaking class; they are STAD and TGT technique. The problem formulations of this research are; (1) Is there any difference influence of STAD and TGT techniques toward students’ speaking performance at tenth grade of SMA N 1 PagarDewa?; (2) Which one is more effective between STAD and TGT techniques toward students’ speaking ability at tenth grade of SMA N 1 PagarDewa?. The research design of this research is True Experimental Design. The population of this research is all of the students of SMA N 1 PagarDewa which consists of eighteen classes with total students are 544 students. The researchers take 58 students from the total population as the sample, where 29 students are in experiment class and 29 students are in control class that be matched based on the students level of speaking ability. The researchers use Cluster Stratified Random Sampling as technique of sampling. To analyze data, the researchers usettestformula. Based on the result of this research and the result of criteria of the hypothesis on the table, the result shows that tCount = 2,8126; moreover the researcher looked at ttable for α = 1% shows ttble = 2.70 and for α = 5% shows ttable = 2.02 or it means tcount>ttable.It is obtained that Ha is accepted while Ho is rejected. It means that there is the difference influence of STAD and TGT technique toward students’ speaking ability and also it means that STAD technique is more effective than TGT technique toward students’ speaking ability. But as the conclusion, both of these techniques are effective to be applied in teaching speaking for the SMA N 1 PagarDewa.